DESIGNING VIDEO LEARNING TO DRAW SIMPLE HOUSE DOOR IN CAD DUA DIMENSI SUBJECT OF PENDIDIKAN TEKNIK BANGUNAN SEBELAS MARET UNIVERSITY - Rahmadi, Didik; Setiawan, Abdul Haris; Roemintoyo, Roemintoyo (Pendidikan Teknik Bangunan, 2013)
ABSTRACTThis research aims to ascertain how to make appropriate learning video as an instrument in CAD Dua Dimensi, including how to make that video and to ascertain the influence towards student?s grades in CAD Dua Dimensi subject of Pendidikan Teknik Bangunan Sebelas Maret University.This research was considered as a research and development (R & D) that was done at Pendidikan Teknik Bangunan Sebelas Maret University. The research?s steps consist of three steps, namely preliminary study, developing design models, and validity of models. 1) Preliminary study was done with descriptive qualitative approach for analyzing necessities of media; 2) Developing design models were done with descriptive approach, namely: a) Making video that consists of three steps, pre-production, production, and post-production. Camtasia Studio 7 was used for making video, then used Adobe Flash CS5 for combining video; b) Trial processing, video was validated by a media expert, a contents expert, and a instructive expert to measured in ratting scale that used for examining appropriateness of media before testing users (alpha testing). Adequate video was tested with experimental method, limited tested and field tested in this method (beta testing) to ascertain the advantage media for users. The data was taken by ratting scale; 3) Summatif testing was used for known the effectiveness of using video towards student?s grades. This step was did by purposive sampling in this experiment, with pre test and post test. The data was analyzed by t-test.The conclution of this research that the video was appropriate for learning according three aspects, 1) Contents, 83% (very good); 2) Instructive, 81% (very good); 3) Media, 81% (very good); 4) The advantage of video, in pre-test 72.58%, in post-test 85.71%; 5) The student?s score especially for drawing simple house door get -5.66 using t-test, the average for pre-test 68.2 and post-test 75.67, the improvement of learning that use video is recomended as an innovation in learning process. This research had some weakness, 1) the process of making media needed long time, the subject only in one odd semester; 2) making perfect of media that used. This research as a motivation to develop learning media in education and as a reference for next researching in institute or other subject. This research must be focus in duration, so the the subtances of subject can reach comprehensively and the learning motivation increase well. Keyword: Learning Media, Learning Video, Simple House Door, CAD 2 Dimensi, Camtasia Studio 7, Adobe Flash CS5